Ethical issues and dilemmas in artificial nutrition and hydration. (February 2021) - Cardenas, Diana
Summary: When the natural oral intake of food and liquids is disturbed the role of caregivers is to assist the patient in order to cover the individual's need for nutrition by nutrition therapy. Nutrition therapy is a medical intervention, which requires an indication for achieving a treatment goal and the informed consent of the competent patient. Withholding and withdrawing nutrition therapy and artificial hydration must be evaluated in specific situations (terminally ill, palliative care, dementia, aged patients) and always case by case according to the patients' cultural and spiritual needs. In the case of ethical issues or dilemmas, application of the four principles of autonomy, beneficence, non-maleficence, and justice is recommended. These principles assist the caregiver in the decision as whether to feed or not to feed. Caregivers must emphasize the right to self-determination and thus to respect the autonomy of the patient, and also the particular vulnerability of the patient suffering from or at risk of malnutrition. Caregivers must be ethically capable of responding to the nutritional needs according to the patient's will and desires even if the patient is not capable of self-determination, always looking for the best benefit to the patient and avoiding harm. Highlights: To identify ethical issues and dilemmas in nutritional therapy. To provide rational justification for ethical decisions in the field of nutrition therapy. To explain the principles of bioethics and its practical approach in the context of clinical nutrition. To identify ethical dilemmas concerning withholding or withdrawing medical nutrition therapy in some specific situations. To enhance ethical reflection in the field of clinical nutrition.